Stillbirth rates and associated risk factors at the Buea and Limbe regional hospitals, Cameroon: a case-control study - Thomas Obinchemti Egbe; Edwin Nkwelle Ewane; Nicholas Tendongfor (BMC, 2020)
Abstract Background Stillbirths bring grief to both mother and family but have been underreported in Cameroon. We aimed at determining the stillbirth rates and associated risk factors in the Buea Regional Hospital (BRH) and the Limbe Regional Hospital (LRH), Cameroon. Materials and methods This was a hospital-based unmatched case-control study in which files of women with stillbirth (cases) were analysed. A woman with a live birth in the same maternity during the same period served as a control. Data were collected using a pre-tested questionnaire. The stillbirth rate was the number of stillbirths per thousand births. Logistic regression analysis was used to identify independent factors associated with stillbirth. Results Stillbirth rates at the BRH and LRH were 33.72 and 36.45 per 1000 live births. The factors that were independently associated with stillbirth were: referral status (AOR 3.95; 95% CI: 1.85-6.58, p = 0.000), late booking visit - after 12 weeks (AOR 13.64; 95% CI: 1.49-124.83, p = 0.021), preeclampsia (AOR 3.21; 95% CI: 1.23-8.35, p = 0.01), placental abruption (AOR 21.46; 95% CI: 2.36-194.77, p = 0.006), moderate anaemia (AOR 2.04; 95% CI: 1.09-3.83, p = 0.03), labour dystocia (AOR 5.37; 95% CI: 1.77-15.92, p = 0.003), low birth weight (AOR 5.27; 95% CI: 1.48-3.53, p = 0.000), and preterm delivery (AOR 2.81; 95% CI: 1.48-3.35, p = 0.002). Conclusion Stillbirth rates are high in both health facilities. Risk factors of stillbirths include referral from another health facility, anaemia, preeclampsia and late booking visit, placental abruption, labour dystocia, preterm birth, and low birth weight. Term, post-term and macrosomia were protective of stillbirth. We recommend electronic data storage in hospitals in Cameroon.